Varieties of Javanese religion : - Beatty, Andrew. (Cambridge University Press, 1999)
Java is famous for its combination of diverse cultural forms and religious beliefs. In this most comprehensive study of Javanese religion since Clifford Geertz's classic study, Andrew Beatty considers Javanese solutions to problems of cultural difference, and how villagers make sense of their complex, multi-layered culture. Pantheist mystics, supernaturalists, orthodox Muslims and Hindu converts at once construct contrasting faiths and create a common ground through syncretist ritual. Vividly evoking the local religious life, this book probes beyond the surface of ritual and cosmology, revealing the compromise inherent in practical religion.